Poincaré recurrence theorem for non-smooth vector fields - Euzébio, Rodrigo D.; Gouveia, Márcio R. A. [UNESP] (Springer Nature, 2017)
In this paper, some ergodic aspects of non-smooth vector fields are studied. More specifically, the concepts of recurrence and invariance of a measure by a flow are discussed, and two versions of the classical Poincaré Recurrence Theorem are presented. The results allow us to soften the hypothesis of the classical Poincaré Recurrence Theorem by admitting non-smooth multivalued flows. The methods used in order to prove the results involve elements from both measure theory and topology.
Keywords: Invariant measure; Non-smooth vector fields; Poincaré Recurrence Theorem